Fractal analysis is a useful tool for evaluating prostate tissue remodeling caused by ethanol consumption and androgen therapy - Lima, Bruna Jardim Pereira; de Oliveira, Gabriel Rodrigues Leal; Sousa, Thainá Cavalleri; de Aquino, Ariana Musa [UNESP]; Hinokuma, Karianne Delalibera; Ricardo, Maria Luiza Silva; Scarano, Wellerson Rodrigo [UNESP]; de Souza Castilho, Anthony César; Pacagnelli, Francis Lopes; Martinez, Francisco Eduardo [UNESP]; de Oliveira Mendes, Leonardo (FapUNIFESP (SciELO), 2023)
Alcohol has been widely consumed for centuries and is linked to the aggravation of diseases. Several studies have shown that excessive consumption of ethanol results in morphophysiological changes in the male reproductive system. One of the effects of ethanol is the decrease in testosterone concentration and hormonal therapies are an alternative to minimize the changes resulting from chronic alcoholism. Qualitative studies were commonly carried out to evaluate the male histopathological alterations resulting from ethanol consumption, being necessary quantitative and non-subjective techniques. This study analyzes the importance of fractal analysis as a useful tool to identify and quantify tissue remodeling in rats submitted to ethanol consumption and hormone therapy with testosterone. Prostate of animals submitted to chronic ethanol consumption showed tissue disorganization, which was confirmed by an increasing of fractal dimension. Regarding the prostatic stroma, collagen fractal dimension and quantification revealed lower values in animals that were only submitted to androgen therapy. Thus, we can conclude that the fractal analysis was a useful tool to quantify tissue changes caused by ethanol consumption and androgen therapy.
Keywords: chronic alcoholism; fractal dimension; prostate; testosterone